The software license unveiled : how legislation by license controls software access - Phillips, Douglas E. (Oxford University Press, 2009)
Nearly every use of a computer is subject not only to public intellectual property law, but also to the privately-written law of the software license. Although the United States has only one Copyright Act and one set of patent laws, there exist thousands of different licenses - to which millions of computer users legally bind themselves by the click of a mouse, usually without reading anything but the word "agree." How do these proliferating but largely unread licenses affect access to software, one of the economy's most valuable resources? In The Software License Unveiled, visionary practitioner Doug Phillips aims to illuminate the unseen law of software to which the software license gives rise.